Wearing a KN95/FFP2 facemask has no measureable effect on functional activity in a challenging working memory n-back task - Montandon, Marie-Louise; Haller, Sven; Rodriguez, Cristelle; Herrmann, François R.; Giannakopoulos, Panteleimon (Frontiers in Human Neuroscience, 2024)
Introduction Wide use of facemasks is one of the many consequences of the COVID-19 pandemic. Methods We used an established working memory n-back task in functional magnetic resonance imaging (fMRI) to explore whether wearing a KN95/FFP2 facemask affects overall performance and brain activation patterns. We provide here a prospective crossover design 3 T fMRI study with/without wearing a tight FFP2/KN95 facemask, including 24 community-dwelling male healthy control participants (mean age ± SD = 37.6 ± 12.7 years) performing a 2-back task. Data analysis was performed using the FSL toolbox, performing both task-related and functional connectivity independent component analyses. Results Wearing an FFP2/KN95 facemask did not impact behavioral measures of the 2-back task (response time and number of errors). The 2-back task resulted in typical activations in working-memory related areas in both MASK and NOMASK conditions. There were no statistically significant differences in MASK versus NOMASK while performing the 2-back task in both task-related and functional connectivity fMRI analyses. Conclusion The effect of wearing a tight FFP2/KN95 facemasks did not significantly affect working memory performance and brain activation patterns of functional connectivity.